Behavioural strategy. Adaptability context = Strategia behawioralna. Kontekst adaptacyjności - Piórkowska, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
The paper is embedded in the following fields: strategic management in terms of behavioural strategy concept, adaptability construct, and micro-foundations realm as well as organizational theory and psychology. Moreover, the paper concerns to some extent a multi-level approach in strategic management involving individual, team, and organizational level.
Keywords: Zarządzanie strategiczne; strategia behawioralna; adaptacyjność; wyniki adaptacyjne; strategic management; behavioural strategy; adaptability; adaptive performance; microfoundations